Ancestry gaps in cardiovascular GWAS: a multi-database review of African representation in genomic studies - Pomales-Matos, Diego A.; Lyerly, Mac; Rivera-Madera, Alejandro; Echevarría-Bonilla, Oswaldo L.; Álvarez-Cortés, Miguel; Henriquez-Quiñones, Saul E.; Reyes-Sosa, Giselle M.; Villanueva-Nogueras, Rafael A.; Peña-Martínez, Edwin G. (Frontiers in Genetics, 2026)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide, claiming millions of lives each year. Genome-wide association studies (GWASs) have identified thousands of CVD-associated variants and have created the foundation for risk assessment and prevention through genetic testing. However, despite all the progress in understanding cardiovascular genomics, our genetic research and findings are overwhelmingly skewed towards individuals of European ancestry. This fact has limited our understanding and effectiveness for the diagnosis and treatment of CVDs in underrepresented populations, such as individuals of African ancestry. This gap is especially consequential because African ancestry populations harbor the greatest global genetic diversity, with variant frequencies and haplotypes that are often poorly captured by current reference datasets. In this review, we highlight recent efforts to understand the effectiveness of current tools in accurately diagnosing and treating CVDs in individuals of African ancestry compared to other populations. Additionally, we also performed a multi-database analysis to explore the persistent diversity gap in cardiovascular genetics. In doing so, we aim to raise awareness about the ancestry gaps faced in disease genomic research, supported by recent findings and the current landscape of our genetic databases.